The F-35 Lightning II : from concept to cockpit - Hamstra, Jeffrey W. (Progress in astronautics and aeronautics, 2019)
The purpose of The F-35 Lightning II: From Concept to Cockpit is to tellthe story of the F-35's technical development - a full spectrum history of the design, development and verification of the F-35 Lightning II as described by the engineers, scientists and managers who were intimately involved throughout the development program. The journey to achieve the F-35's extraordinary capability was long with untold challenges encountered on the path. The reader will.